The Spectrality of Technology and the Gendered Subjugation in Stephen King’s Mr. Mercedes: Spektralitas Teknologi dan Penaklukan Gender dalam “Mr. Mercedes” Karya Stephen King - Subramanian, Sridheepika Varadareddiar (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
This study examines Stephen King’s Mr. Mercedes as a techno-horror narrative in which technology operates as a spectral force that reinforces patriarchal domination. Combining the issue of gendered subjugation with the objective of analyzing its technological mechanisms, this research investigates how digital tools function as invisible yet pervasive instruments of control. Using a qualitative textual analysis grounded in Goldman’s concept of spectral reading and Faulkner’s gendered technology framework, the study explores how Brady Hartsfield weaponizes surveillance, digital manipulation, and remote intimidation to harm and dominate women, particularly Holly and Janey. The findings reveal that technology in the novel exceeds its function as a mere tool; it becomes a ghostly presence that destabilizes privacy, autonomy, and psychological security. Through this portrayal, King critiques the insidious forms of violence enabled by technological mediation and exposes the heightened vulnerability of marginalized individuals in digitized environments. The study concludes that Mr. Mercedes operates as a contemporary parable of invisible power structures regulating modern gender relations through technological means.